EEG findings in CAR T-cell-associated neurotoxicity: Clinical and radiological correlations. Issue 2 (15th July 2021) - Beuchat, Isabelle; Danish, Husain H; Rubin, Daniel B; Jacobson, Caron; Robertson, Matthew; Vaitkevicius, Henrikas; Lee, Jong Woo
Abstract: Background: While EEG is frequently reported as abnormal after chimeric antigen receptor (CAR) T-cell therapy, its clinical significance remains unclear. We aim to systematically describe EEG features in a large single-center cohort and correlate them with clinical and radiological findings. Methods: We retrospectively identified patients undergoing CAR T-cell therapy who had continuous EEG. Neurotoxicity grades, detailed neurological symptoms, and brain MRI or FDG-PET were obtained. Correlation between clinical and radiological findings and EEG features was assessed. Results: In 81 patients with median neurotoxicity grade 3 (IQR 2–3), diffuse EEG background slowing was the most common finding and correlated with neurotoxicity severity ( P <.001). A total of 42 patients had rhythmic or periodic patterns, 16 of them within the ictal-interictal-continuum (IIC), 5 with clinical seizures, and 3 with only electrographic seizures. Focal EEG abnormalities, consisting of lateralized periodic discharges (LPD, n = 1), lateralized rhythmic delta activity (LRDA, n = 6), or focal slowing ( n = 19), were found in 22 patients. All patients with LRDA, LPD, and 10/19 patients with focal slowing had focal clinical symptoms concordant with these EEG abnormalities. In addition, these focal EEG changes are often correlated with PET hypometabolism or MRI hypoperfusion, in absence of a structural lesion. Conclusion: In adult patients experiencing neurotoxicity after CAR T-cell infusion, EEG degree of background disorganization correlated with neurotoxicity severity. IIC patterns and focal EEG abnormalities are frequent and often correlate with focal clinical symptoms and with PET-hypometabolism/MRI-hypoperfusion, without structural lesion. The etiology of these findings remains to be elucidated.